Acid hydrolysis of glycosidic bonds in oat β‐glucan and development of a structured kinetic model. Issue 7 (8th March 2018) - Nguyen, Hoang S. H.; Heinonen, Jari; Sainio, Tuomo
Abstract : Homogeneous acid‐catalyzed hydrolysis of oat β‐glucan, which contains β‐(1, 4) and β‐(1, 3) glycosidic bonds in a nonrandom order, was studied at 353 K using HCl and H2 SO4 . A new structured kinetic model was developed that takes into account the difference in the reactivity of β‐(1, 4) and β‐(1, 3) glycosidic bonds as well as their positions in the polysaccharide chain. To minimize the correlation of adjustable parameters in the new model, the reactivities of these bonds were studied independently (T = 313…363 K; cH+  = 0.1…2 mol/L) using cellobiose and laminaribiose. The difference in kinetic parameters (e.g., T = 338 K: kβ‐(1, 4)  = 0.693 × 10 −3 L/mol/min, kβ‐(1, 3)  = 1.027 × 10 −3 L/mol/min) was found to be statistically significant (P < 0.0001), which emphasizes the need for the structured model for oat β‐glucan hydrolysis. The simulation of β‐glucan hydrolysis with the new model was in good agreement with the experimental data and shows improvement over existing nonstructured models . © 2018 American Institute of Chemical Engineers AIChE J, 64: 2570–2580, 2018